LESSON STUDY PENGEMBANGAN BAHAN PEMBELAJARAN BERBASIS POTENSI LOKAL UNTUK MENINGKATKAN KOMPETENSI PROFESIONAL GURU SD DI KABUPATEN KEBUMEN - Rokhmaniyah Rokhmaniyah; Kartika Christy Surandari (Universitas PGRI Madiun, 2016)
This study aims to: (1) apply lesson study in the development of learning materials based on local potential to improve the professional competence of primary school teachers in Kebumen in 2016; (2) produce learning materials based on local potential through lesson study as an effort to improve the professional competence of elementary school teachers in Kebumen in 2016. This study overall approach development (Research and Development / R & D). These research subjects were elementary school teachers in Kebumen numbered 50 people. Selection of study subjects according to the school characteristics, was by observing the accreditation status of the school and teacher status. The collection of data were through (1) Focus Group Discussion (FGD). (2) observation, (3) test, (4) study the documentation, (5) interview, (6) checklish behavior, and (7) video. It can be concluded: (1) Lesson study based on learning materials development of local potential improve the professional competence of elementary school teachers in Kebumen 2015. (2) Lesson study can produce learning materials based on local potential quality. Improving the quality of the results of the implementation of lesson study the development of learning materials based on local potential to improve the professional competence of elementary school teachers in Kebumen 2015 reached 90%.Keywords: professional competence, lesson study, the local potential.